Phenotypic Conversions of “Protoplasmic” to “Reactive” Astrocytes in Alexander Disease - Sosunov, Alexander A. (Society for Neuroscience, 2013)
Alexander Disease (AxD) is a primary disorder of astrocytes, caused by heterozygous mutations in GFAP, which encodes the major astrocyte intermediate filament protein, glial fibrillary acidic protein (GFAP). Astrocytes in AxD display hypertrophy, massive increases in GFAP, and the accumulation of Rosenthal fibers, cytoplasmic protein inclusions containing GFAP, and small heat shock proteins. To study the effects of GFAP mutations on astrocyte morphology and physiology, we have examined hippocampal astrocytes in three mouse models of AxD, a transgenic line (GFAP(Tg)) in which the normal human GFAP is expressed in several copies, a knock-in line (Gfap(+/R236H)) in which one of the Gfap genes bears an R236H mutation, and a mouse derived from the mating of these two lines (GFAP(Tg); Gfap(+/R236H)). We report changes in astrocyte phenotype in all lines, with the most severe in the GFAP(Tg);Gfap(+/R236H), resulting in the conversion of protoplasmic astrocytes to cells that have lost their bushy-like morphology because of a reduction of distal fine processes, and become multinucleated and hypertrophic. Astrocytes activate the mTOR cascade, acquire CD44, and lose GLT-1. The altered astrocytes display a microheterogeneity in phenotypes, even neighboring cells. Astrocytes also show diminished glutamate transporter current, are significantly depolarized, and not coupled to adjacent astrocytes. Thus, the accumulation of GFAP in the AxD mouse astrocytes initiates a conversion of normal, protoplasmic astrocytes to astrocytes that display severely “reactive” characteristics, many of which may be detrimental to neighboring neurons and oligodendrocytes.